A Mix of Old British and Modern European Breeds: Genomic Prediction of Breed Composition of Smallholder Pigs in Uganda - Babigumira, Brian Martin; Sölkner, Johann; Mészáros, Gábor; Pfeiffer, Christina; Lewis, Craig R. G.; Ouma, Emily; Wurzinger, Maria; Marshall, Karen (Frontiers in Genetics, 2021)
Pig herds in Africa comprise genotypes ranging from local ecotypes to commercial breeds. Many animals are composites of these two types and the best levels of crossbreeding for particular production systems are largely unknown. These pigs are managed without structured breeding programs and inbreeding is potentially limiting. The objective of this study was to quantify ancestry contributions and inbreeding levels in a population of smallholder pigs in Uganda. The study was set in the districts of Hoima and Kamuli in Uganda and involved 422 pigs. Pig hair samples were taken from adult and growing pigs in the framework of a longitudinal study investigating productivity and profitability of smallholder pig production. The samples were genotyped using the porcine GeneSeek Genomic Profiler 50K SNP Chip. The SNP data was analyzed to infer breed ancestry and auto zygosity of the Uganda pigs. The results showed that exotic breeds (modern European and old British) contributed an average of 22.8% with a range of 2-50%11.3±7.8% while ‘local’ blood contributed 69.2% (36.9-95.2%)69.4±13.8% to the ancestry of the pigs the study area of Uganda. Runs of homozygosity (ROH) greater than 2 megabase (Mb) quantified the average genomic inbreeding coefficient of the Uganda pigs as 0.0430.036. The scarcity of long ROH indicated low recent inbreeding. We conclude that the genomic background of the pig population in the study is a mix of old British and modern pig ancestries.